(untitled) (Canadian Perspectives on Academic Integrity, 2023)
The concept of academic integrity in post-secondary institutions has many faces. It can be considered as a lack of student ethics to be dealt with by policy when the time comes. As something that instructors are expected to unilaterally maintain within their own classrooms. As an institutional norm, or as an impossible utopia. Without a national quality assurance body to inform their efforts, Canadian colleges and universities can look to England and Australia for guidance on academic integrity. The Quality Assurance Agency (QAA) and Tertiary Education Quality and Standards Agency (TEQSA) guide both of these countries respectively, while providing a wealth of information to those living and working elsewhere, including Canada. In 2020, QAA recommended that institutions designate the coordination of academic integrity to new or existing positions within post-secondary institutions. There remains, however, “limited opportunities for formalized training for academic integrity” (Vogt & Eaton, 2022, p.24). As such, Canadians working in post-secondary academic integrity come from diverse areas and disciplines, including academic support units, libraries, student advocacy, test centres, and many others. Some work is done off the side of desks, while some institutions have academic integrity offices with specialized staff. In this moderated panel session, academic integrity practitioners and professionals from various Canadian institutions will reflect on their work and the future of academic integrity in Canadian colleges and universities, deepening current understandings and providing a vision for others.